Self-appraisal adequacy of students’ physical abilities of pedagogical specialties involved in various forms of education - V.V. TSYBUL’SKA (Physical Education of Students, 2014)
Purpose : considered self-appraisal adequacy of students’ physical abilities of students of pedagogical specialties involved in various forms of education. Material : the study was conducted with students of II and IV courses of the Faculty of Primary Education stationary and correspondence courses (total 120 people.). Used a technique of self-appraisal of physical development, technique of rapid assessment of physical health, motor tests. Results : set the direction for the development of the values of physical culture and self-improvement of physical abilities that depend on the adequacy of the self-assessment of their physical development and physical fitness. The comparison of subjective and objective indicators for assessing physical health and physical fitness of students. Highlighted significant differences in the direction of re-evaluation of their physical abilities in students of correspondence courses. Conclusions : It is recommended to use the self-appraisal methodology of physical development to determine the degree of objectivity of self-confidence, which determines the motivation for self-improvement.